Linchpin : are you indispensible? - Godin, Seth. (New York : Portfolio, 2010)
The bestselling author of'Tribes' and'The Dip' returns with his most powerful book yet in which he explores why some people make a difference in their fields--and others don't.
The new world of work -- Thinking about your choice -- Indoctrination: how we got here -- Becoming the linchpin -- Is is possible to do hard work in a cubicle? -- The resistance -- The powerful culture of gifts -- There is no map -- Making the choice -- The culture of connection -- The seven abilities of the linchpin -- When it doesn't work.
Includes bibliographical references (p. [238]-244)
Keywords: Employee motivation; Employees -- Attitudes; Creative thinking; Value added; Work -- Psychological aspects